Tourism and Crime: an Exploratory Study of Burglary From Tourist Accommodation From the Criminal Opportunity Perspective - Vakhitova, Zarina (Crime & delinquency, 2023)
It is widely acknowledged that tourists are particularly likely to be victimized, especially with regard to property crimes like theft from tourist accommodation (burglary). Guided by the criminal opportunity perspective, we examine the extent to which environmental and routine activities-related factors explain burglary using the data from a sample of Australian tourists (N?=?1,027). Bayesian variable selection with a stochastic search algorithm was used to analyze the data. Our findings demonstrate the utility of opportunity theories in explaining crime against tourists. We found that the location and type of accommodation together with the use of target hardening and guardianship strategies are helpful for understanding burglary from tourist accommodation. Practical implications for crime prevention are also discussed.